PENGAWASAN SOSIAL TERHADAP REMAJA DI KELURAHAN SIMPANG KANAN KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR (Studi Pada Pelaku Tindak Kriminal) - Sulastri Devi; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Simpang Kanan Village, Simpang Kanan District, Rokan Hilir Regency. The problem studied is, what causes teenagers to commit a crime? And what about social supervision of juvenile offenders? The purpose of this research is to know the cause of the happening of adolescent doing crime, and to know how social supervision to adolescent perpetrator of crime. Subjects in this study amounted to 13 (thirteen) people, who were the parents of criminals, community leaders and the police. Researchers use the theory of deviance, labeling theory and social control theory. The author uses Qualitative method Descriptive, which describes the phenomena that occur in the field according to the actual situation with the process of resolving the problem based on the existing situation in the field. And using purposive sample technique, which means the technique of taking the subject as well as data sources with certain considerations. Which subject is determined to suit the research theme. From the results of this study adolescents who commit criminal acts such as taking drugs, stealing and torture has a cause of free association, lack of economy and lack of social supervision. Some of the perpetrators who stole the results for daily needs other than that the perpetrators who consume drugs and torture due to lack of social oversight of close and remote monitoring such as various information when a child does not go home. The social environment of juvenile offenders is very lack of social oversight and lack of attention from parents, and lack of education such as religious and moral decency in which the teenagers develop.Keywords: Social Monitoring, Youth, Crime